Design of Molecular Transformations Based on the Concerted Function of Two Zinc Atoms in Bis(iodozincio)methane - Sada, Mutsumi; Uchiyama, Masanobu; Matsubara, Seijiro (Synlett, 2014)
Bis(iodozincio)methane, prepared from diiodomethane and zinc metal in the presence of a lead catalyst, is capable of performing several unique molecular transformations. It can operate not only as a dianion, but also as a bidentate Lewis acid. In this account, the methylenation of carbonyl compounds, nucleophilic cyclopropanation reactions, 1,4-addition reactions of bis(iodozincio)methane, and reduction reactions of π-allylpalladium are discussed, along with the associated density functional theory calculations.1 Introduction2 Methylenation of Carbonyl Compounds3 Nucleophilic Cyclopropanation3.1 Cyclopropanation of 1,2-Diketones3.2 Asymmetric Construction of Quaternary Carbon Atoms by Stereospecific Cyclopropanation4 1,4-Addition Reactions of Bis(iodozincio)methane4.1 Three-Atom Ring-Contraction Reaction4.2 Enolate–Homoenolate Intermediates and Their Reactions5 Reduction of π-Allylpalladium Derivatives6 Conclusions and Outlook
Keywords: zinc; dizinc; cyclopropanation; oxy-Cope rearrangement; 1,4-addition; organometallic reagents; ring contractions; π-allylpalladium